SENSIBILIDADE DE Trichoderma harzianum AO GLIFOSATO E À ATRAZINA - PUCHETA, Renan Mancoelho; BLANCO, Neder Henrique Martinez; SILVA, Talísia de Souza; COSTA, Brenda Fernandes; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2024)
-